Análise da percepção ambiental de atores sociais do município de Balneário Camboriú-SC - Frasson, Vanise da Rosa (2011)
Environmental perception is the way in which an individual perceives the environment. If each person has a history, a life experience, their perceptions are also different, it is inconsistent to valuate this perception right or wrong, even if the situations are exactly the same. In this sense, the personal experience contributes in a singular way to the people´s conception of the world. However, the high media exposition of issues related to sustainability, global warming, melting glaciers, and others environmental problems, make these subjects very popular and people may get confused about how to deal with it. Many times the population receives too much information about global issues or even contradictories information about ecologism. Even ecologically friendly people feel powerless and hopeless in front of too much information. This fact influences in citizenship actions, in other words, suppress the individual the necessity of become aware of a conflicting situation and to develop a movement to the collective interest. Thus, the proposal intend to analyze the environmental perception in Balneário Camboriú SC, verifying in which way the information overplus about ecology influence in this process and in the citizenship action. The research was developed in two types of investigation, based on Vicente del Rio essay, Cidade da Mente, Cidade Real: percepção ambiental e revitalização na area portuária do RJ. It is important to highlight that in addition to the investigation proposal, it was used the theoretical principals of phenomenology and methodological of the discourse analysis. The results show that there is a series of projects and environmental campaign, but they do not reach people awareness. Furthermore, perceptions show that the environmental problematic in the city is perceived as a result of an intensive process of urbanization. Looking at the bibliographic investigation and at the methodological procedures it can be inferred that individual environmental perception is very helpful to understand and create citizenship actions related to the environment.